The Influence Marketing Mix and Service Quality Towards Word of Mouth and Ride-Service Platform Usage - Rena Yuliana; Agus Rahayu; Heny Hendrayati (Westscience Press, 2023)
This study aims to analyze the effect of Marketing Mix and service quality on Word-of-Mouth (WoM) and usage behavior of online transportation service platforms. The research is descriptive with the sampling technique used is simple random sampling, through a survey conducted on 382 samples using questionnaires as research instruments. There are four latent variables in this study, namely marketing mix and service quality as independent variables, word of mouth as intervening variables and use of travel service platforms as dependent variables. The descriptive data obtained was processed using SPSS 24 and the Structural Equation Modeling (SEM) data was processed using SMART PLS. The findings from this study provide insight to online transportation service platform providers in optimizing marketing strategies and improving service quality to increase platform usage. The practical implications of these results can lead to increased user retention and long-term business growth.